Iconographic Considerations on the Paintings of the Hall of the Kings in the Alhambra of Granada - Vallejo Naranjo, Carmen (Eikón / Imago, 2014)
The quality and supranational vocation of chivalric culture as unique ideological- moral code of ethics of life valid for all the aristocratic structure, that effectively transcended the Christian world, was fully expressed through his own artistic production. His aesthetic ability did that his ideology and moral values overstepped physical, cultural and religious boundaries. The chivalric language became the one language of consensuated representation for socio- political relations both of feudal nature as well as between kingdoms, being its ceremonial scenic the canal proper for development of diplomatic relations of the court. This fact is further enshrined in the field of visual arts where its iconography meet directly and globally the representative function of the various aspects that constitute and demarcate the warlike nature of the medieval aristocracy and her aesthetic mode of life, whose apotheosis is the chivalrous pomp. Hunt days and games that actually promote political relations and are, ultimately, the diplomatic framework that expresses the difficult medieval balances of power. In this key we have interpreted the painted ceiling of the Hall of the Kings in the Alhambra of Granada.